Nationalism in the translated literary titles during the Japanese occupation: A study of Djawa Baroe - Idrus, Idrus; Hiraishi, Noriko; Anwar, Fithyani; Sonezza, Ladyanna; Helmita, Helmita (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study investigates the representation of nationalism in the translation of literary titles published in Djawa Baroe, an Indonesian-language magazine circulated during the Japanese occupation from 1942 to 1945. It focuses on the translation strategies and ideological meanings conveyed through lexical choices and symbolic narratives. The analysis identifies twenty-six translated titles, examining three representative examples in detail to illustrate how linguistic adaptation intersects with nationalist discourse. Employing Vinay and Darbelnet’s translation model, the study distinguishes between direct and oblique strategies to explain how titles were modified to fit Indonesian conventions while resonating with nationalist sentiments. Additionally, Fairclough’s Critical Discourse Analysis (CDA) situates these strategies within broader ideological and socio-political contexts, allowing the research to capture micro-level textual operations and reveal how translation acted as discourse production embedded within wartime power structures. Findings demonstrate that translators utilized deliberate techniques such as modulation, equivalence, and orthographic adjustment to enhance readability and embed ideological content, foregrounding themes of patriotism, sacrifice, and devotion to the motherland. This highlights that translation in Djawa Baroe was far from a neutral linguistic transfer; instead, it emerged as a politically charged act of cultural mediation. By illustrating how Japanese occupation propaganda intersected with Indonesian nationalist discourse through translation, this study contributes to translation studies by underscoring the ideological role of translation as an instrument of power, identity, and cultural hegemony.